Assessing good governance in procurement at the Lejweleputswa District Municipality - Stemele, Bulumko Mollman (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPA (School of Public Management and Planning))--University of Stellenbosch, 2009.